Some Techniques to Improve Speaking and Writing Skills - Edmundo Mora (Asociación Colombiana de Profesores de Ingles, 2016)
Through the years, English teachers have often expected their students to be able to use English fluently both orally and in written form. This of course, sounds like a very real and practical goal to reach. In fact, not in vain have linguists called speaking and writing the productive skills of the language as it is through them that learners can demonstrate how much English they have readily available at their disposal to interact with people in a real context.